1976
DOI: 10.1128/aac.10.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Ribavirin Given by the Intraperitoneal or Aerosol Route Against Influenza Virus Infections in Mice

Abstract: Ribavirin (1-,8--ribofuranosyl-1,2,4-triazole-3-carboxamide) is an effective antiviral agent against type A influenza infection of mice. Therapy was most effective when administered as a small-particle aerosol early in the infection. Treatment was also effective by either the intraperitoneal or aerosol route in mice with histological evidence of pneumonia. Ribavirin increased the percent survival, lowered lung virus titers, and decreased the development of lung pathology when therapy was initiated at 6 h as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
2

Year Published

1977
1977
1988
1988

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
(20 reference statements)
0
24
2
Order By: Relevance
“…These experiments indicated that small-particle aerosols (mass median diameter, 1.4 gm) of ribavirin were more effective in reducing mortality, lesions in the lung, and virus concentrations in the lungs than approximately equivalent doses of drug given intraperitoneally (i.p.) (4). However, the data did not indicate how much better aerosol administration was than i.p.…”
mentioning
confidence: 50%
See 3 more Smart Citations
“…These experiments indicated that small-particle aerosols (mass median diameter, 1.4 gm) of ribavirin were more effective in reducing mortality, lesions in the lung, and virus concentrations in the lungs than approximately equivalent doses of drug given intraperitoneally (i.p.) (4). However, the data did not indicate how much better aerosol administration was than i.p.…”
mentioning
confidence: 50%
“…Recently, ribavirin (1-3-D-ribofuranosyl-1,2,4-triazole-3-carboxamide) was found to be effective for the treatment of type A influenza virus infections in mice (1,(3)(4)(5). These experiments indicated that small-particle aerosols (mass median diameter, 1.4 gm) of ribavirin were more effective in reducing mortality, lesions in the lung, and virus concentrations in the lungs than approximately equivalent doses of drug given intraperitoneally (i.p.)…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Amantadine, rmantadine, and ribavirin have demonstrated activity against disease caused by several strains of type A influenza virus (6,8,9,12,13). This paper reports results of studies on the efficacy of these three drugs given by the oral route for the prevention and/or treatment of type A/New Jersey (swine) influenza virus infections in mice.…”
mentioning
confidence: 99%